Importance of WASH Interventions in Tackling Stunting and Wasting Problems in Children - Steffany Soegijanto; Jessica Natalie Santoso; Angelica Gabriel Eldyjoe; Bernadeth Caecilya Anggraini Halim; Timothy Sastra; Zenlly Erenn Jossevynne; Figo Valentino; Junaida Astina (Universitas Bio Scientia Internasional Indonesia, 2025)
Child malnutrition is a serious health condition caused by insufficient or excessive consumption of calories, carbohydrates, fats, proteins, vitamins, and minerals. Poor sanitation, hygiene, and viral infections directly related to malnutrition, which also correlated with stunting and wasting. UNICEF and WHO work globally to combat malnutrition, especially stunting and wasting, by implementing WASH programs to minimize diarrheal illnesses and improve nutritional status. Despite encouraging results, WASH interventions face several limitations such as resource demand and adaptation to unforeseen circumstances. Some recommendations for future programs include combining WASH with nutritional education, growth tracking, community engagement, and supplements for better results. To alleviate stunting in children, infrastructure, hygiene education, and public cleanliness should be improved. Taking a holistic approach to physical and cognitive development is essential to solving the complicated issue of child malnutrition, especially in Indonesia.